Tourism Village Digitalization Strategy to Increase the Diversification of Tourist Attractions in Lebakmuncang Village, Ciwidey District - Pratama, Armandha Redo; Sukriah, Erry; Hindayani, Purna; Ihsan, Haikal Muhammad; Marhanah, Sri (Universitas Pendidikan Indonesia, 2024)
ABSTRACTLebakmuncang Tourism Village, Ciwidey District requires an adaptation in increasing the diversification of tourist attractions. Comprehensive and attractive digitalization needs to be carried out to maximize the promotion of Tourism Villages. This research aims to analyze digitalization strategies that are suitable for implementation in the Lebakmuncang Tourism Village with a diversification approach to tourist attractions. The method used in this research is descriptive qualitative with the variable diversification of tourist attractions which has indicators of Tourist Village Structure, potential for tourist attractions, Sapta Pesona, homestay management, digital marketing and digitalization of virtual tours. Based on the analysis, it was found that the challenges faced by the Lebakmuncang Tourism Village are based on minimal management knowledge and the lack of development of existing information media, apart from that the management has not been optimal in improving the branding image of the tourist village through the use of technology. You can diversify tourist attractions in the Lebakmuncang Tourism Village by creating a 360 virtual tour scheme. Virtual tour technology using a 360 camera can be a solution for digitizing tourist attractions in the Lebakmuncang tourist village. Six indicators of the diversification variable of tourist attractions can be created into a 360 virtual tour scheme, which offers authenticity and virtual experience of tourist attraction locations.ABSTRAKDesa Wisata Lebakmuncang, Kecamatan Ciwidey membutuhkan suatu adaptasi dalam peningkatan diversifikasi atraksi wisata. Digitalisasi secara komprehensif dan menarik perlu dilakukan untuk memaksimalkan promosi Desa Wisata. Penelitian ini bertujuan untuk menganalisis strategi digitalisasi yang cocok di terapkan di Desa Wisata Lebakmuncang dengan pendekatan diversifikasi atraksi wisata. Metode yang dilakukan pada penelitian ini yaitu kualitatif deskriptif dengan variabel diversifikasi atraksi wisata yang memiliki indikator strukur Desa Wisata, potensi atraksi wisata, sapta pesona, pengelolaan homestay, pemasaran digital dan digitalisasi virtual tour. Berdasarkan analisis ditemukan bahwa tantangan yang dihadapi pada Desa Wisata Lebakmuncang berporos pada pengetahuan tatakelola yang minim dan belum berkembangnya media informasi yang ada, selain itu juga pengelola belum optimal dalam meningkatkan branding image desa wisata melalui pemanfaatan teknologi. Teknologi virtual tour menggunakan kamera 360 dapat menjadi solusi untuk digitalisasi atraksi wisata di Desa Wisata Lebakmuncang. Enam indikator dari variabel diversifikasi atraksi wisata dapat dibuat skema virtual tour 360, yang dimana menawarkan keaslian serta pengalaman secara virtual lokasi atraksi wisata.